Factors Affecting Passenger Satisfaction at Terminal B Kabanjahe - Saragih, Afrida Natalia; Revida , Erika; Trimurni, Februati (PERSPEKTIF, 2024)
This research aims to analyze the factors influencing passenger satisfaction at Terminal B Kabanjahe. The study adopts a quantitative approach with a descriptive method, and the data analysis employs SPSS software version 22. The results reveal a positive influence of factors such as product quality, service quality, and emotional factors on passenger satisfaction at Terminal B Kabanjahe. However, there is no significant influence found between price and cost factors and passenger satisfaction at the terminal. Furthermore, when considered simultaneously, product quality, service quality, emotional factors, price, and cost collectively contribute to 44.50% of passenger satisfaction, while the remaining 55.50% is influenced by other external factors beyond the study's model. Other contributing factors to passenger satisfaction involve location, promotion, brand image, reputation, trust, and various other aspects.